Sensitivity Analysis and Simulation of a Multiserver Queueing System with Mixed Service Time Distribution - Evsey Morozov; Michele Pagano; Irina Peshkova; Alexander Rumyantsev (Mathematics, 2020)
The motivation of mixing distributions in communication/queueing systems modeling is that some input data (e.g., service time in queueing models) may follow several distinct distributions in a single input flow. In this paper, we study the sensitivity of performance measures on proximity of the service time distributions of a multiserver system model with two-component Pareto mixture distribution of service times. The theoretical results are illustrated by numerical simulation of the <semantics>M/G/c</semantics> systems while using the perfect sampling approach.